2017
DOI: 10.3892/mmr.2017.7959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silencing TEM8 gene on proliferation, apoptosis, migration and invasion of XWLC‑05 lung cancer cells

Abstract: Currently, the role of tumor endothelial marker 8 (TEM8) in the occurrence, development, invasion and metastasis of lung cancer and its mechanism are poorly understood. The present study aimed to investigate the effects of TEM8 on proliferation, apoptosis, migration and invasion of XWLC-05 lung cancer cells. The expression of TEM8 in human lung cancer and adjacent tissues was detected by reverse transcription-quantitative polymerase chain reaction and western blotting. An interference vector coding a short hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Since angiogenesis is a major hallmark of cancer, researchers have investigated the roles of CMG2 and TEM8 in cancer since their initial discovery. For TEM8, the literature is consistent in that its overexpression results in more aggressive cancer, especially for osteosarcomas 52 , gallbladder carcinomas 53 , melanomas 42 , and lung 54 , breast 55, 56 , and colorectal 57 cancers. However, for CMG2, there are mixed reports of the effect of its overexpression on cancer progression; some show that lower CMG2 correlated with a more aggressive soft-tissue sarcoma 58 and breast cancer 59 , and others reveal that higher CMG2 resulted in a worse survival rate in patients with gastric cancer 60 and glioblastoma 61 .…”
Section: Converging Physiological Functions Of Anthrax Toxin Receptorsmentioning
confidence: 78%
“…Since angiogenesis is a major hallmark of cancer, researchers have investigated the roles of CMG2 and TEM8 in cancer since their initial discovery. For TEM8, the literature is consistent in that its overexpression results in more aggressive cancer, especially for osteosarcomas 52 , gallbladder carcinomas 53 , melanomas 42 , and lung 54 , breast 55, 56 , and colorectal 57 cancers. However, for CMG2, there are mixed reports of the effect of its overexpression on cancer progression; some show that lower CMG2 correlated with a more aggressive soft-tissue sarcoma 58 and breast cancer 59 , and others reveal that higher CMG2 resulted in a worse survival rate in patients with gastric cancer 60 and glioblastoma 61 .…”
Section: Converging Physiological Functions Of Anthrax Toxin Receptorsmentioning
confidence: 78%
“…Therefore, the function of Antxr1 in the proliferation of endothelial cells differs between physiological conditions and cancer angiogenesis. Furthermore, knockdown of Antxr1 reduced the proliferation of osteosarcoma and XWLC05 lung adenocarcinoma cells [31,32]. Thus, Antxr1 positively regulates the proliferation of both endothelial cells in cancer and the cancer cells themselves but negatively regulates endothelial cell proliferation in physiological conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, ANTXR1 has previously been found to be specifically expressed in the tumor microenvironment . In the context of cancer, ANTXR1 is upregulated in diverse cancer types and plays an important role in tumor development, such as lung cancer, breast cancer, and gallbladder carcinoma . In addition, Shukla et al observed that ANTXR1 was expressed in 10.4% of T2 tumors, 79.5% of T3 tumors, and 84.8% of T4 tumors .…”
Section: Discussionmentioning
confidence: 99%